Contextual Teaching and Learning: A Practical Approach to Improving Hospitality Students’ Speaking Skills - Hana Yulinda Fithriyani; Puput Dewi Anggraeni (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Contextual teaching and learning (CTL) is recognized as a teaching approach rooted in real-world situations. This research aimed to assess whether the application of CTL can enhance the speaking abilities of hospitality students. The study utilized classroom action research with a total of 27 participants. Participants were chosen through a purposive sampling method. Data collection involved three techniques, including tests, observations, and interviews. The assessment tools utilized in this research comprised authentic assessments, observation checklists, and interview questionnaires. The data were subsequently analyzed using reduction analysis techniques. The findings indicated that in the initial test, only 59.26% of students achieved speaking scores above the benchmark score. In cycle 1, there was an improvement of 25.93%, followed by an additional 29.63% increase in cycle 2. This demonstrates that CTL can effectively aid students in enhancing their speaking skills.